Morinda citrifolia Inhibits Both Cytosolic Ca(2+)-dependent Phospholipase A(2) and Secretory Ca(2+)-dependent Phospholipase A(2) - Song, Ho Sun (The Korean Physiological Society and The Korean Society of Pharmacology, 2010)
This study investigated the effects of the methanol extracts of Morinda citrifolia containing numerous anthraquinone and iridoid on phospholipase A(2) (PLA(2)) isozyme. PLA(2) activity was measured using various PLA(2) substrates, including 10-pyrene phosphatidylcholine, 1-palmitoyl-2-[(14)C]arachidonyl phosphatidylcholine ([(14)C]AA-PC), and [(3)H]arachidonic acid (AA). The methanol extracts suppressed melittin-induced [(3)H]AA release in a concentration-dependent manner in RAW 264.7 cells, and inhibited cPLA(2)/sPLA(2)-induced hydrolysis of [(14)C]AA-PC in a concentration- and time-dependent manner. A Dixon plot showed that the inhibition by methanol extracts on cPLA(2) and sPLA(2) appeared to be competitive with inhibition constants (K(i)) of 3.7µg/ml and 12.6µg/ml, respectively. These data suggest that methanol extracts of Morinda citrifolia inhibits both Ca(2+)-dependent PLA(2) such as, cPLA(2) and sPLA(2). Therefore, Morinda citrifolia may possess anti-inflammatory activity secondary to Ca(2+)-dependent PLA(2) inhibition.